SOCIETAL TRANSFORMATION THROUGH SYSTEM INTEGRATION AND WORKFLOW AUTOMATION: A MULTIDIMENSIONAL ANALYSIS OF PUBLIC SERVICES AND WORKFORCE DYNAMICS - Ranadheer Suram, (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
This article examines the comprehensive societal impact of system integration and workflow automation, particularly emphasizing public service delivery and workforce transformation. The article investigates how automated systems reshape job roles, influence economic productivity, and enhance public services across governmental agencies and healthcare sectors. The article explores the delicate balance between technological advancement and human capital development by analyzing workforce adaptation strategies and upskilling initiatives. The article addresses critical ethical considerations, including data privacy concerns and job displacement implications, while evaluating the resilience of automated systems in crisis management. Special attention is given to transforming healthcare delivery and public safety systems through automation. The findings reveal significant implications for policymakers, organizational leaders, and workforce development strategists, contributing to the broader understanding of societal adaptation in an increasingly automated environment. This article provides valuable insights into optimizing human-automation interaction and recommends sustainable integration of automated systems in public service delivery.